Arthritogenicity of annexin VII revealed by phosphoproteomics of rheumatoid synoviocytes. Issue 8 (17th May 2011) - Matsuo, Kosuke; Arito, Mitsumi; Noyori, Koji; Nakamura, Hiroshi; Kurokawa, Manae S; Masuko, Kayo; Okamoto, Kazuki; Nagai, Kouhei; Suematsu, Naoya; Yudoh, Kazuo; Beppu, Moroe; Saito, Tomoyuki; et al.
Abstract : Objective: To identify novel proteins involved in the pathogenesis of rheumatoid arthritis (RA) and to characterise the identified proteins based on pathogenic and therapeutic aspects. Methods: The authors applied differential phosphoproteomic analysis to articular synoviocytes between RA and osteoarthritis (OA) to identify proteins differently phosphorylated between RA and OA. Focusing on annexin VII (Anx7), one of the highly phosphorylated proteins in RA, the authors prepared Anx7 -transgenic C57BL/6 ( Anx7 -Tg-B6) mice to evaluate their susceptibility to collagen-induced arthritis (CIA). In addition, the authors examined the effect of anti-Anx7 antibodies (Abs) on CIA and serum levels of cytokines in wild-type DBA/1J mice, which are known to be susceptible to CIA, and in Anx7 -Tg-B6 mice. In vitro, the authors examined the effect of the Anx7 knockdown by small interfering RNA on the secretion of cytokines in rheumatoid synoviocytes and the human synovial sarcoma cell line SW982. Results: The Anx7 transgene altered the CIA-resistant B6 mice to CIA-susceptible ones. The Abs treatment suppressed CIA even in the wild-type DBA/1J mice. The serum levels of cytokines including interleukin 6 (IL-6) and TNFα were not altered by the Abs treatment in vivo. On the other hand, the knockdown of Anx7 by small interfering RNA caused downregulation of IL-8 secretion in vitro. Conclusions: These results indicate that Anx7 participates in the pathogenesis of RA partly through the secretion of IL-8. The study data have demonstrated the pathogenic roles and therapeutic significance of Anx7 in RA for the first time.